2015
DOI: 10.1002/elsc.201400194
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan and hydroxyapatite composite cross‐linked by dopamine has improved anisotropic hydroxyapatite growth and wet mechanical properties

Abstract: Synthetic hydroxyapatite (HAp) has been used due to its excellent biocompatibility and chemical similarity to natural bone. Increasing aspect ratio of the synthetic HAp particle is one of the main concerns regarding tissue engineeringbecausenatural bone is a composite consisting of HAp nanorods.Here, we found the HAp particles grow anisotropically in a needle shape with an aspect ratio of ~4.4 in the presence of chitosan and dopamine. The HAp particles with high aspect ratio could be used for curing dentin sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 45 publications
(75 reference statements)
1
4
0
Order By: Relevance
“…The reason for the decrease in hydrogel swelling and degradation rates is the same as mentioned above: the large number of active groups on PHA increased the cross‐linking density of the hydrogel, preventing excessive swelling of the hydrogels and delaying its degradation. Prajatelistia, Lim, Oh, Jun, and Hwang ()) used DA as an agent to cross‐link nHA and chitosan, and the results showed that the addition of DA reduced swelling in the presence of water, which is consistent with the results of our study. The swelling properties observed here are suitable for clinical applications, not only to fill the defect site but also to prevent harm from excessive spillover of the hydrogel material.…”
Section: Resultssupporting
confidence: 89%
“…The reason for the decrease in hydrogel swelling and degradation rates is the same as mentioned above: the large number of active groups on PHA increased the cross‐linking density of the hydrogel, preventing excessive swelling of the hydrogels and delaying its degradation. Prajatelistia, Lim, Oh, Jun, and Hwang ()) used DA as an agent to cross‐link nHA and chitosan, and the results showed that the addition of DA reduced swelling in the presence of water, which is consistent with the results of our study. The swelling properties observed here are suitable for clinical applications, not only to fill the defect site but also to prevent harm from excessive spillover of the hydrogel material.…”
Section: Resultssupporting
confidence: 89%
“…The pyrogallol group of GA binds to calcium ions in aqueous environments, which is a similar mechanism to catecholamines, which bind and enrich the interface with Ca 2+ , and this facilitates the precipitation of HAp crystals . Thus, GA/metal ion complex in the tubule was expected to accelerate a remineralized HAp in the presence of saliva.…”
Section: Resultsmentioning
confidence: 99%
“…Bone mineralization involves HAp crystal deposition on a preexisting organic matrix consisting of type‐I collagen excreted from osteoblastic cells. Collagen aids crystal formation therein and acts as a support for ionic species, while HAp precipitates from aqueous solutions, as demonstrated by in vitro studies . Additionally, collagen obtained from demineralized bone grafted in combination with HAp is an excellent osteoinductive material .…”
Section: Introductionmentioning
confidence: 99%